2014
DOI: 10.2753/ree1540-496x5001s113
|View full text |Cite
|
Sign up to set email alerts
|

Investment Performance of Individual Investors: Evidence from the Korean Stock Market

Abstract: We use unique equity holdings data for each type of investor to investigate the relationship between individual investors' shareholdings and variables such as corporate characteristics and stock returns in the Korean stock market. We find that stocks with the highest individual holdings underperform stocks with the lowest individual holdings. This return difference is attributable to individual investors' uninformed stock-picking skills resulting from lack of attention given to or misinterpretation of readily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Similar results for a broader group of 34 countries, which included both emerging and developed markets, were reported byThomas et al (2014), who found that pension funds as institutional investors can contribute to the reduction of stock market volatility.3 In a different study that used the data from South Korea, which is directly relevant to the literature on the trading activity of various types of investors, Park and Kim (2014) investigated equity holdings of individual investors and found that stocks with the highest proportion of individual holdings underperform stocks with the lowest proportion of individual holdings. This difference in returns was explained by individual investors' uninformed stock-picking skills resulting from the lack of attention given to, or misinterpretation of, the readily accessible firm fundamentals data Park and Kim (2014). also argue that the characteristics of stocks favoured by individual investors are associated with small capitalization, low stock price, low profitability and high turnover.Pension funds, large capital inflows and stock returns in a thin market…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results for a broader group of 34 countries, which included both emerging and developed markets, were reported byThomas et al (2014), who found that pension funds as institutional investors can contribute to the reduction of stock market volatility.3 In a different study that used the data from South Korea, which is directly relevant to the literature on the trading activity of various types of investors, Park and Kim (2014) investigated equity holdings of individual investors and found that stocks with the highest proportion of individual holdings underperform stocks with the lowest proportion of individual holdings. This difference in returns was explained by individual investors' uninformed stock-picking skills resulting from the lack of attention given to, or misinterpretation of, the readily accessible firm fundamentals data Park and Kim (2014). also argue that the characteristics of stocks favoured by individual investors are associated with small capitalization, low stock price, low profitability and high turnover.Pension funds, large capital inflows and stock returns in a thin market…”
mentioning
confidence: 99%
“… 3 In a different study that used the data from South Korea, which is directly relevant to the literature on the trading activity of various types of investors, Park and Kim (2014) investigated equity holdings of individual investors and found that stocks with the highest proportion of individual holdings underperform stocks with the lowest proportion of individual holdings. This difference in returns was explained by individual investors’ uninformed stock-picking skills resulting from the lack of attention given to, or misinterpretation of, the readily accessible firm fundamentals data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The system in developing economies may cause information asymmetry between individual and institutional investors due to inadequate policies for investor protection and disclosures. Individual investors in Korea have been observed to underperform due to their weak skills in stock selection (Park & Kim, 2014). Forecasting performance of fund may help investors to mitigate risks and maximize returns over the same (Gu, 2021).…”
Section: Investment Performance Vol 4 Issue 2 Issn (Online): 2790-77...mentioning
confidence: 99%
“…Some of the recent works, for example, investment performance and investor sentiment, information content of implied volatility index, behavioral investment strategy and volatility spillover effects (e.g. Ryu, 2012;Narayan et al, 2014;Park and Kim, 2014;Taşdemir and Yalama, 2014;Uygur and Taş, 2014;Jain-Chandra and Unsal, 2014;Padhi, 2014a, b, c, 2015). But, we do not find any study in the emerging markets like India that deals with the investor's "fear" and "greed" index.…”
Section: Review Of Earlier Studiesmentioning
confidence: 99%